Pemilihan Guru Terbaik di Era Digital Berdasarkan Kompetensi dengan Metode AHP (Analytic Hierarchy Process) pada SD Negeri Kebon Manggis 01 - Eko Denny Suseno; Michael Sonny; Han Sulaiman (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study discusses the development and implementation of a Decision Support System (DSS) for selecting the best teacher at SD Negeri Kebon Manggis 01 using the Analytic Hierarchy Process (AHP) method. The main problems identified include teacher performance evaluations that are still largely subjective, the absence of structured competency standards, and limited transparency in the process of determining the best teacher. These conditions may lead to inconsistent evaluation results and dissatisfaction among teachers.AHP was chosen because it is effective for solving multi-criteria decision-making problems by organizing criteria into a hierarchical structure and applying pairwise comparisons. In this study, the evaluation criteria consist of pedagogical competence, professional competence, personal competence, and social competence. Data were collected through observation, questionnaires, and documentation. The collected data were then processed to determine the priority weights of each criterion and to calculate the final scores for each teacher candidate.The results indicate that the implementation of AHP produces a more objective and consistent ranking of teachers. The developed DSS also improves the efficiency of data processing and provides recommendations that are fair, transparent, and accountable. Therefore, this system can serve as a strategic solution for schools to enhance teacher performance assessment and improve educational quality in the digital era.